The manuscript of Nuzhat al-Absar wa Juhaynat al-Akhbar by Ibn Abi al-Surur al-Bakri (998 AH- 1087 AH): Historical study and verification / Saleh Muhammad Zeki Mahmood - Saleh Muhammad Zeki , Mahmood (2019)
This thesis is majoring in the History and Islamic civilization studies and it is titled as: (The Manuscript of Nuzhat al-Absar wa Juhaynat al-Akhbar by Ibn Abi al-Surur al-Bakri (998 AH- 1087 AH) : Historical Study and Verification.). This thesis studies only the part about the Abbasid period starting from the regimen of Abu Al Abbas Al Safah and ending by the regimen of Al Musta'sim Billah (132 AH to 656 AH). The main objectives of this study is to verify the attribution of this manuscript to Ibn Abi al-Surur Al Bakri, the location of other copies if any, clarifying the distinction between the copies and describing it thoroughly, introducing Ibn Abi al-Surur Al Bakri and providing very accurate information about him, identify his views and the historical information in this manuscript. This allowed this study to reveal the great scientific value that distinguishes this manuscript. In this study, the researcher pursued the descriptive method rather than the comprehensive investigation method. This study was done on two parts, studying and verification of the manuscript. The most prominent results the researcher was able to verify is that this manuscript is indeed one of the works of Ibn Abi al-Surur Al Bakri. It was also confirmed with evidence that the Book of Nuzhat al-absar wa-juhaynat al-akhbār had no other than the two copies which this study in based on. The specific part of Abbasid period was fully investigated highlighting the most important historical views that Al Bakri was known for. The researcher advises the graduate students of the importance of studying and investigating the rest of Ibn Abi Surur Al Bakri’s books.